THE CONTRIBUTION OF PONDOK PESANTREN RIYADHUL JANNAH IN EMPOWERING THE COMMUNITY ECONOMY IN THE VILLAGE OF PACET MOJOKERTO - Rifqi Lazuardian; Irham Zaki (Universitas Airlangga, 2020)
This study aims to analyze the role of the Riyadhul Jannah Islamic Boarding School in community economic empowerment in Pacet Village, Mojokerto. This study uses a qualitative research approach to understand phenomena about what is experienced by research subjects, such as subjects, perceptions, motivations, actions, and so forth. The results showed that the Riyadhul Jannah Islamic boarding school had a role in community empowerment around the boarding school. The role of Islamic boarding schools is shown by the activities of the business units of PT. Rijan Dinamis Selaras which involve communities around the boarding schools so that the benefits can be felt directly by the people of Pacet Village and its surroundings.Keywords: Economic Empowerment, Islamic Business, Islamic CommunitiesREFFERENCE Dhofier, Zamakhsyari Dhofier. (2011). Tradisi pesantren studi tentang pandangan hidup kyai. Jakarta: LP3ES.G, Sumudiningrat. (2000). Visi dan misi pembangunan pertanian berbasis pemberdayaan. Yogyakarta: IDEA.Steenbrink, Karel. (1986). Pesantren madrasah sekolah, pendidikan islam dalam kurun modern. Jakarta: Dharma Aksara.Hirokoshi, Hiroko. (1987). Kiai dan perubahan sosial. Jakarta: Perhimpunan Pengembangan Pesantren dan Masyarakat (P3M).Fauroni, Lukman. R. (2014). Model bisnis ala pesantren: Filsafat ukhuwah menembus hypermarket memberdayakan ekonomi umat. Yogyakarta: Kaukaba.Soekamto, Soerjono. (2009). Sosiologi suatu pengantar. Jakarta: Rajawali Press.Qomar, Mujamil. (2008). Pesantren: Dari transformasi metodologi menuju demokrasi institusi. Jakarta: Penerbit Erlangga.Madjid, Nurcholis. (1997). Bilik-bilik pesantren: Sebuah potret perjalanan. Jakarta: Paramadina.Maulana, Mirza. Al-Kautsari. (2014). Pemberdayaan masyarakat berbasis pondok pesantren (studi pondok pesantren ASWAJA lintang songo desa sitimulyo, piyungan, Bantul). Skripsi tidak diterbitkan. Yogyakarta: Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Sunan Kalijaga.Yin. Robert. K. (2008). Studi kasus: Desain dan metode. Jakarta: PT. Raja Grafindo.